Алгоритм придушення паразитної кутової модуляції - Михальова, А. Г. (ХНУРЕ, 2024)
The algorithm for suppression of parasitic angular modulation in radio electronic equipment designed for the enrichment of ore with a useful substance that has active conductivity is considered. It is shown that the procedures of this algorithm are based on bandpass, low-pass filtering, and product operations, which allows for practical implementation of the proposed real-time algorithm in both analog and digital formats. It is noted that this algorithm can be im proved by processing the original oscillation in quadrature.
Keywords: придушення паразитної модуляції; кутова модуляція